1997
DOI: 10.1097/00007890-199705270-00021
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cd26/Dipeptidyl Peptidase Iv Activity in Vivo Prolongs Cardiac Allograft Survival in Rat Recipients1,2

Abstract: The CD26 antigen, one of the major costimulatory molecules in T cell activation, was shown to possess dipeptidyl peptidase IV (DPP IV) activity. Previously, we demonstrated that immunosuppressed kidney transplant patients exhibit lower DPP IV serum activity as compared with healthy individuals. In the present study, we analyzed the role of CD26/DPP IV in the immune cascade triggered by organ transplantation and leading to acute rejection of cardiac allografts in rat recipients. Transplantation of hearts from (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 22 publications
1
62
1
Order By: Relevance
“…3). Our conclusion is further supported by a recent study in a rat transplantation model (47). Treatment with the irreversible DP IV inhibitor prodipine prevented the increase in serum DP IV normally seen during the first days after cardiac allotransplantation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…3). Our conclusion is further supported by a recent study in a rat transplantation model (47). Treatment with the irreversible DP IV inhibitor prodipine prevented the increase in serum DP IV normally seen during the first days after cardiac allotransplantation.…”
Section: Discussionsupporting
confidence: 85%
“…Treatment with the irreversible DP IV inhibitor prodipine prevented the increase in serum DP IV normally seen during the first days after cardiac allotransplantation. Both allograft rejection and the concomitant increase of DP IV activity in transplant tissue were delayed (47). In another study, arthritis signs in rats could be suppressed by several biochemically distinct DP IV inhibitors, including I49, indicating that the effect was very likely to be due to the specific inhibitory effect on DP IV (48).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the enzymatic activity in the immunoregulatory function of CD26/ DPP IV is demonstrated under several circumstances. These include the in vitro normalization of impaired responses to recall antigens by the addition of soluble CD26/DPP IV (6,7) and the in vivo suppression of immune activation upon alloantigen challenge by specific CD26/DPP IV inhibitors (8). Recently, CD26/DPP IV has been shown to process the NH 2 terminus of a number of chemokines including RANTES, granulocyte chemotactic protein-2 (GCP-2), and SDF-1, generating naturally occurring truncated molecules with a significantly altered biological activity (9 -12).…”
Section: Dipeptide Generating Mdc(5-69) This Second Cleavage After mentioning
confidence: 99%
“…The CD26 molecule functions as the cell membrane-associated exopeptidase dipeptidyl peptidase (DP) 4 IV (EC 3.4.14.5), an enzyme capable of cleaving N-terminal dipeptides from polypeptides with either proline or alanine residues at the penultimate position (1)(2)(3). Many recent reports have demonstrated that CD26/DP IV serves as an important regulator of immune responses by affecting T cell activation, proliferation, and cytokine production (1)(2)(3)(4)(5)(6)(7)(8). Subsequently, multiple roles were predicted for CD26/DP IV in leukocyte homing and inflammation.…”
mentioning
confidence: 99%